The role of islet autoantigen-specific T cells in the onset and treatment of type 1 diabetes mellitus - Yue, Mengmeng; He, Xianzhen; Min, Xinwen; Yang, Handong; Xu, Hao; Wu, Wenwen; Zhong, Jixin; Mei, Aihua; Chen, Jun (Frontiers in Immunology, 2024)
Type 1 diabetes mellitus (T1DM), a complex chronic disease with an intricate etiology and pathogenesis, involves the recognition of self-antigens by pancreatic islet autoantigen-specific T cells and plays crucial roles in both early- and late-stage destruction of beta cells, thus impacting disease progression. Antigen-specific T cells regulate and execute immune responses by recognizing particular antigens, playing broad roles in the treatment of various diseases. Immunotherapy targeting antigen-specific T cells holds promising potential as a targeted treatment approach. This review outlines the pathogenesis of diabetes, emphasizing the pivotal role of pancreatic islet autoantigen-specific T cells in the progression and treatment of T1DM. Exploring this avenue in research holds promise for identifying novel therapeutic targets for effectively managing diabetes.